Effects of intense physical training on left ventricular hemodynamic forces in endurance athletes: A feature-tracking cardiac magnetic resonance study - Rakhmanov, Y.; Jumadilova, D.; Toktarbay, B.; Khamitova, Z.; Zhankorazova, A.; Zholshybek, N.; Khissamutdinov, N.; Bekbossynova, M.; Dautov, T.; Salustri, A. (Medicine & Science in Sports & Exercise, 2025)
Purpose We sought to evaluate the effect of intensive physical training on left ventricular (LV) hemodynamic forces (HDF) in athletes.